Karakteristik Enkapsulat Ekstrak Etanol Kulit Apel Rome Beauty (Malus sylvestris Mill.) dengan Perlakuan Perbandingan Maltodekstrin dan Gum Arab - Chandra, Fiona; Yusasrini, Ni Luh Ari; Puspawati, Gusti Ayu Kadek Diah (Jurnal Ilmu dan Teknologi Pangan (ITEPA), 2024)
Rome beauty apple peel is an industrial waste that remains rich in bioactive components. One of the ways to utilize these bioactive components is through extraction and encapsulation. Encapsulation is a technique that involves covering bioactive components with a coating material. Each coating material, such as maltodextrin, has its own drawbacks, thus it often needs to be combined with other coating materials to achieve optimal encapsulation characteristics. The objective of this research is to determine the effect of different ratios of maltodextrin to gum arabic on the characteristics of the encapsulated ethanol extract from rome beauty apple peel and to identify the optimal ratio of maltodextrin to gum arabic for achieving encapsulate with the best characteristics. This research employs a Completely Randomized Design (CRD) with treatments involving different ratios of maltodextrin to gum arabic in six levels: P0 (10:0), P1 (9:1), P2 (7:3), P3 (5:5), P4 (3:7), and P5 (1:9). Each treatment was replicated three times, resulting in 18 experimental units. The data obtained were analyzed using analysis of variance (ANOVA), and when the treatments affected the observed variables, Duncan’s Multiple Range Test (DMRT) was employed for further analysis. The results of this research show that the ratio of maltodextrin to gum arabic significantly affects yield, moisture content, solubility, total phenols, total flavonoids, antioxidant activity, encapsulation efficiency, and the morphology of encapsulate. The maltodextrin to gum arabic ratio (1:9) produced encapsulates with the best characteristics, consist of a 78.40 percent yield, 9.22 percent moisture content, 87,39 percent of solubility, 31.79 mg GAE/g total phenols, 2.35 mg QE/g total flavonoids, 70.24 percent antioxidant activity, 92.99 percent encapsulation efficiency, and a smooth, non-porous surface morphology. Keywords: encapsulation, gum arabic, rome beauty apple peel, maltodextrin